MAGMA GENERATION AND MIXING IN THE EARLIEST VOLCANIC CENTRE OF SANTORINI (AKROTIRI PENINSULA). MINERAL CHEMISTRY EVIDENCE FROM THE AKROTIRI PYROCLASTICS - Kitsopoulos, K. (Bulletin of the Geological Society of Greece, 2010)
Santorini is a dominant expression of magma generation and subsequent volcanism in the Meditereanean area, where a calk-alkaline, high-alumina, basalt-andesite-dacite type of volcanism was expressed from eight centres. The volcanics of the Akrotiri peninsula are considered to be the products of the earliest (Pliocene Pleistocene) volcanic centre. The present study has investigated the mineral chemistry of some major pyrogenic phenocrysts, such as plagioclase and Fe-Ti oxides, of the Akrotiri pyroclatics unit, which have undergone a notable zeolitization procedure. The results are compatible with magma mixing mechanism of a primitive mantle derived, saturated, of mafic composition component with silicic magma in shallow crustal depths.